«Вольное переложение» Жития Феодора Студита "Free transposition" of The Life of Theodore Studite - Tamara P. Lönngren (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2012)
This article deals with the manuscript tradition named "free transposition" applied to The Life of Theodore Studite in Old Russian literature. Evidence is presented that the author of this "free transposition" was indeed Nil Sorskij. The investigation of eight recently discovered copies has made it possible to establish their mutual interdependence and to construct the corresponding stemma.